2022
DOI: 10.3389/fgene.2022.938488
|View full text |Cite
|
Sign up to set email alerts
|

Cuproptosis scoring model predicts overall survival and assists in immunotherapeutic decision making in pancreatic carcinoma

Abstract: Background: Cuproptosis is a newly identified form of non-apoptotic cell death that is associated with the progression and treatment responses in pancreatic adenocarcinoma (PAAD). However, its impact on oncology and tumor microenvironment (TME) remains unclear.Methods: Hub genes were identified using least absolute shrinkage and selection operator (LASSO) Cox regression for 25 newly reported cuproptosis-related regulators and subjected to stepwise regression to obtain cuproptosis-related score (CuRS). Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…DLD was considered as a risk factor in studies of different tumors such as uveal melanoma(UVM), glioma, and LUAD [ 129 , 139 , 143 , 183 ]. In contrast, LIAS was analyzed as a protective factor in studies of UVM, glioma, and pancreatic adenocarcinoma(PAAD) [ 139 , 142 , 156 158 ]. In studies, DLAT was analyzed as a PAAD risk factor [ 156 158 ] and conversely was considered to be associated with a protective effect in glioma [ 142 , 143 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…DLD was considered as a risk factor in studies of different tumors such as uveal melanoma(UVM), glioma, and LUAD [ 129 , 139 , 143 , 183 ]. In contrast, LIAS was analyzed as a protective factor in studies of UVM, glioma, and pancreatic adenocarcinoma(PAAD) [ 139 , 142 , 156 158 ]. In studies, DLAT was analyzed as a PAAD risk factor [ 156 158 ] and conversely was considered to be associated with a protective effect in glioma [ 142 , 143 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, LIAS was analyzed as a protective factor in studies of UVM, glioma, and pancreatic adenocarcinoma(PAAD) [ 139 , 142 , 156 158 ]. In studies, DLAT was analyzed as a PAAD risk factor [ 156 158 ] and conversely was considered to be associated with a protective effect in glioma [ 142 , 143 ]. Even in different studies on the same tumor, different investigators considered FDX1 and PDHA1 as risk or protective factor respectively [ 129 , 130 , 148 , 149 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also assessed model reliability by decision curve analysis, and in comparison to the extreme curves, benefit of both RiskScore and Nomogram was significantly greater and the two showed a stronger survival prediction (Figure 9I). Herein, we selected three risk models from previous studies (5gene signature (Yan) (Yan et al, 2022), 3-gene signature (Yang) (Yang et al, 2022) and 9-gene signature (Liu) (Liu et al, 2022)) to compare with our model. In order to make the model have a certain comparability, the same method is used to calculate the sample risk score according to the corresponding genes in the three models, and zscore is performed for Riskscore.…”
Section: Riskscore In Combination With Clinicopathological Features T...mentioning
confidence: 99%
“…Not surprisingly, the oxidative phosphorylation inhibitor Gboxin analog was found to have a strong proliferation inhibitory and cell cycle blocking effect on DLBCL with specific selectivity for it ( 34 ). Several recent studies have revealed the potential role of CRGs in the prognosis of cancers, such as kidney cancer ( 35 42 ), hepatocellular carcinoma ( 43 47 ), lung cancer ( 48 53 ), head and neck squamous cell carcinoma ( 53 60 ), glioma ( 61 66 ), breast cancer ( 67 70 ), endometrial carcinoma ( 71 , 72 ), melanoma ( 73 75 ), pancreatic cancer ( 76 , 77 ), colorectal cancer ( 78 81 ) and so on. However, no reports describe any effects of the cuproptosis regulatory mechanism on DLBCL.…”
Section: Introductionmentioning
confidence: 99%